2020
DOI: 10.3390/molecules25092259
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of High-Performance Bamboo–Plastic Composites Reinforced by Natural Halloysite Nanotubes

Abstract: Bamboo-plastic composites (BPCs) as new biomass-plastic composites have recently attracted much attention. However, weak mechanical performance and high moisture absorption as well as low thermal stability greatly limit their industrial applications. In this context, different amounts of halloysite nanotubes (HNTs) were used as a natural reinforcing filler for BPCs. It was found that the thermal stability of BPCs increased with increasing HNT contents. The mechanical strength of BPCs was improved with the incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…For composite samples, the value of CYP is the lowest for ECMBF‐5 (18.12%). This could be due to increased physical interaction between bamboo fillers and epoxy resin 35 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For composite samples, the value of CYP is the lowest for ECMBF‐5 (18.12%). This could be due to increased physical interaction between bamboo fillers and epoxy resin 35 …”
Section: Resultsmentioning
confidence: 99%
“…This two-step degradation process can be categorized into the temperature ranges of 200-300 C and 400-500 C. The first degradation can be attributed to the decomposition of bamboo fillers aided by depolymerization of the cellulosic contents present in the bamboo fillers. 35,36 the second step of degradation above 400 C can be associated with the degradation of epoxy polymer matrix. It can be noticed that there is not any significant initial degradation due to the evaporation of moisture around 100 C like it was seen for the BFs.…”
Section: Thermal Degradation Analysis Of Bfs and Compositementioning
confidence: 99%
“…BPC breaks through the limitations of traditional bamboo applications and represents a highquality and high-value-added method of utilizing bamboo. BPC integrates the advantages of bamboo and plastic materials, such as high wear resistance, green construction and environmental protection, and good chemical and mechanical properties [2][3][4]. BPC is used in many fields, including in construction, packaging, furniture, and decoration [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In literature, several research works 2,7,11,14-21 have reported on use of multi component polymer blends to toughen the natural fibre reinforced polymer composite material. However, there are very few works which describe the effect of reinforcement percentage variation along with elastomer addition 20,21 and there are no works which discuss the effect of elastomer addition in bamboo polymer composites with homopolymer and copolymer matrix.…”
Section: Introductionmentioning
confidence: 99%
“…The decrease in flexural properties was attributed to the low interfacial bonding between CNT and matrix polymer. Jin et al 19 investigated the effect of addition of Halloysite Nanotube (HNT) in BPC. Thermal stability of BPCs improved with increasing HNT contents.…”
Section: Introductionmentioning
confidence: 99%